2016
DOI: 10.1183/13993003.02018-2015
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing primary ciliary dyskinesia: an international patient perspective

Abstract: Primary ciliary dyskinesia (PCD) is a rare genetic disorder characterised by progressive sino-pulmonary disease, with symptoms starting soon after birth. A European Respiratory Society (ERS) Task Force aims to address disparities in diagnostics across Europe by providing evidence-based clinical practice guidelines. We aimed to identify challenges faced by patients when referred for PCD diagnostic testing.A patient survey was developed by patient representatives and healthcare specialists to capture experience.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 31 publications
1
68
1
4
Order By: Relevance
“…The patient representatives to the Task Force fully endorsed that an accurate diagnosis was an important outcome, because it leads to a better recognition of their problems by physicians and more effective treatment, and thus improves their health and quality of life. This was confirmed by our questionnaire survey of 352 PCD patients from 25 countries, and 20 in-depth interviews [7]. However, diagnostic accuracy studies do not provide direct evidence for the improvement of patient-important outcomes; consequently, the confidence in results of test accuracy studies was judged at best as moderate.…”
Section: Methodsmentioning
confidence: 61%
See 1 more Smart Citation
“…The patient representatives to the Task Force fully endorsed that an accurate diagnosis was an important outcome, because it leads to a better recognition of their problems by physicians and more effective treatment, and thus improves their health and quality of life. This was confirmed by our questionnaire survey of 352 PCD patients from 25 countries, and 20 in-depth interviews [7]. However, diagnostic accuracy studies do not provide direct evidence for the improvement of patient-important outcomes; consequently, the confidence in results of test accuracy studies was judged at best as moderate.…”
Section: Methodsmentioning
confidence: 61%
“…Evidence from patients does not alter the strength of published evidence but was considered when deciding the strength of recommendations. The Task Force conducted a questionnaire survey of 352 PCD patients from 25 countries, and 20 in-depth interviews [7]. Patients told us that an accurate diagnosis was an important outcome, leading to a better recognition of their problems by physicians and access to effective treatment, thus improving their health and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…An international survey of 271 PCD patients reported 37% had over 40 visits to medical professionals due to PCD-related symptoms before being referred for testing [28]. The most prevalent symptoms in PCD are not disease specific; perhaps not surprisingly, patients with situs inversus, a rare condition in the general population [29], are diagnosed at an earlier age [17].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the majority of patients presenting with NRS [5], studies have shown that neonates are rarely diagnosed with PCD [2,17], nor are they referred early for testing [28]. MULLOWNEY et al [6] demonstrated that the combination of lobar collapse, situs inversus and/or persistent oxygen therapy for over 2 days in term newborns with respiratory distress can accurately predict PCD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation